SUN-LB018 Role of BMAL1 in Western Diet-Induced Disruption of Circadian Hypothalamic Feeding Neuropeptides - Clemenzi, Matthew (J Endocr Soc, 2019)
Circadian rhythms drive the timing of daily physiological functions, including food intake. These cellular rhythms depend on the intricate regulation of core clock genes, such as BMAL1. Disruptions of the molecular clock in rodents have been shown to induce obesity and features of the metabolic syndrome, as well as altering diurnal food intake patterns. In vitro studies using palmitate, a saturated fatty acid comprising a large portion of high-fat diets, demonstrate alterations in hypothalamic BMAL1 and feeding-related neuropeptide expression. We hypothesized that the high-fat, high-sugar (Western) diet alters circadian food intake rhythms by altering hypothalamic feeding-related neuropeptide expression in a BMAL1-dependent manner. C57BL/6-J mice were fed either rodent chow (RC; control) or Western diet (WD) for 16 weeks. Male and female WD mice gained more weight compared to controls, and consumed a larger proportion of their food during the inactive (light) period. Hypothalamic mRNA expression patterns of neuropeptide Y (NPY), agouti-related peptide (AgRP), and proopiomelanocortin (POMC) were markedly altered by WD feeding. Compared to RC controls, WD mice showed a blunted mRNA expression of AgRP and NPY, accompanied by an altered hypothalamic expression of the clock genes BMAL1 and Per2. To identify the cellular mechanism by which the WD affects the central control of food intake, hypothalamic cell lines were derived from adult BMAL1-wildtype (WT) and knockout (KO) C57BL/6-J mice. Hypothalamic primary cultures were immortalized with SV40 T-antigen and characterized to demonstrate a robust rhythmic cycling of clock gene expression, in addition to the expression of several neuropeptides. Importantly, BMAL1-WT neurons exhibited a 24-hour period in Per2 clock gene mRNA expression, while the BMAL1-KO cell line lacked rhythmic expression of Per2, confirming the cell line as a hypothalamic model of circadian disruption. Additionally, the expression patterns of NPY, AgRP, and POMC were altered with BMAL1 knockout. Treatment with palmitate increased BMAL1, Per2, and POMC expression at 9 or 21 hours, corresponding to the peak and trough of clock and neuropeptide mRNA expression. Taken together, these results suggest a role for the circadian clock in regulating hypothalamic neuropeptide expression and, thereby, central control of food intake. Sources of research support: MNC has received graduate awards from the Banting and Best Diabetes Centre and the Ontario Graduate Scholarship; studies were supported by CIHR and NSERC operating grants. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.